Management of large mediastinal masses: surgical and anesthesiological considerations - Li, Wilson W.L.; van Boven, Wim Jan P.; Annema, Jouke T.; Eberl, Susanne; Klomp, Houke M.; de Mol, Bas A.J.M. (Journal of Thoracic Disease; Vol 8, No 3 (March 18, 2016): Journal of Thoracic Disease, 2016)
Large mediastinal masses are rare, and encompass a wide variety of diseases. Regardless of the diagnosis, all large mediastinal masses may cause compression or invasion of vital structures, resulting in respiratory insufficiency or hemodynamic decompensation. Detailed preoperative preparation is a prerequisite for favorable surgical outcomes and should include preoperative multimodality imaging, with emphasis on vascular anatomy and invasive characteristics of the tumor. A multidisciplinary team should decide whether neoadjuvant therapy can be beneficial. Furthermore, the anesthesiologist has to evaluate the risk of intraoperative mediastinal mass syndrome (MMS). With adequate preoperative team planning, a safe anesthesiological and surgical strategy can be accomplished.